2014
DOI: 10.1155/2014/836921
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Program to Improve Self-Management of Patients with Heart Failure by Redesigning Care Coordination

Abstract: Objectives. We tested both an educational and a care coordination element of health care to examine if better disease-specific knowledge leads to successful self-management of heart failure (HF). Background. The high utilization of health care resources and poor patient outcomes associated with HF justify tests of change to improve self-management of HF. Methods. This prospective study tested two components of the Chronic Care Model (clinical information systems and self-management support) to improve outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…O doente com insuficiência cardíaca sofre alterações a nível do seu autocuidado e para que haja melhoria na qualidade de vida é fundamental que estes doentes tenham conhecimento da sua doença e consigam reconhecer os sinais e sintomas de agravamento (6,7) . Só com este conhecimento conseguem fazer uma gestão adequada do autocuidado (20) . É também tendo como base este conhecimento que se evitam os reinternamentos e o recurso à urgência por descompensação (11,20) .…”
Section: Discussão De Resultadosunclassified
See 2 more Smart Citations
“…O doente com insuficiência cardíaca sofre alterações a nível do seu autocuidado e para que haja melhoria na qualidade de vida é fundamental que estes doentes tenham conhecimento da sua doença e consigam reconhecer os sinais e sintomas de agravamento (6,7) . Só com este conhecimento conseguem fazer uma gestão adequada do autocuidado (20) . É também tendo como base este conhecimento que se evitam os reinternamentos e o recurso à urgência por descompensação (11,20) .…”
Section: Discussão De Resultadosunclassified
“…Só com este conhecimento conseguem fazer uma gestão adequada do autocuidado (20) . É também tendo como base este conhecimento que se evitam os reinternamentos e o recurso à urgência por descompensação (11,20) .…”
Section: Discussão De Resultadosunclassified
See 1 more Smart Citation
“…One study 138 did not (described below). Two studies 105,140 found that care planning during and after the transition from secondary to primary care reduces readmission rates, and another two 86,105 that having operational facilitators to support care planning reduced readmission rates.…”
Section: Causal Link 10:9 -Contextsmentioning
confidence: 99%
“…This intervention did indeed make patients more likely to monitor their weight and change their health behaviours, but no less likely to be admitted or re-admitted to hospital. 140 A SR 105 of transitional care interventions found that three components of care were associated with reduced short-term admission rates: (1) care co-ordination by a nurse (most frequently a registered nurse or advanced-practice nurse), (2) a home visit within 3 days and (3) communication between the hospital and the primary care provider. Most of the interventions in the review that reduced intermediate-and long-term readmissions involved care co-ordination.…”
Section: Causal Link 10:9 -Contextsmentioning
confidence: 99%